PERSEPSI MASYARAKAT TERHADAP RENCANA PENGEMBANGAN EKOWISATA HUTAN BONGOK DI DESA JETAK KECAMATAN MONTONG KABUPATEN TUBAN - Jereng, Indra; Asnah, Asnah; Rofiatin, Umi (Universitas Tribhuwana Tunggadewi, 2023)
The study aimed to determine the publics perception of the ecotourism development plan in the Bongok protected forest and determine the factors that encourage and hinder the plan to develop Bongok forest ecotourism. This research uses a descriptive method approach. Data collection techniques using observation, interviews or questionnaires, and documentation. Community perceptions of the development of Bongok forest ecotourism according to the results of the recapitulation of perceptions of the community for the development of ecotourism researchers explained that public perceptions of plans to develop Bongok forest ecotourism with the following percentages such as public perception of the development of Bongok forest tourism objects with an average value of 85.12%, community perceptions related to the development of ecotourism facilities 89.82% and public perception regarding the development of the Bongok forest ecotourism function averaged 87.23%. Factors driving the development of bongok forest ecotourism are geographic factors, human Resources factors, sociocultural factors and institutional strengthening factors. The other factors that hinder the process of developing ecotourism are minimal funds and facility factor